Oh, the things you can find (if only you analyze): a close textual analysis of Dr. Seuss' rhetoric for children - Lange, Kendall N. (Kansas State University, 2009)
This study seeks to discover the loci, or themes, within the post-World War II books of Theodor Geisel, whom generations of American readers came to know as “Dr. Seuss.” A prolific children's author and social activist, Dr. Seuss penned more than 40 children’s books during the period under investigation. After World War II, Seuss’ books began to merge social themes with his entertaining storylines and trademark illustrations. This thesis applies a methodology that draws from both close textual analysis and topically-oriented critical approaches in order to illuminate loci in 10 selected works. Through Cicero’s critical process of invention, relationships between arguments and loci are established. Analysis of these “message books” reveals the complex political and ideological themes present in Dr. Seuss’ texts while situating his work within a larger American rhetorical tradition of didactic children’s literature.
Keywords: loci; close textual analysis; rhetorical criticism; Dr. Seuss; topical approaches; Theodor Geisel; Speech Communication (0459)